Achieving Ultrahigh Energy‐Density Aqueous Supercapacitors via a Novel Acidic Radical Adsorption Capacity‐Activation Mechanism in Ni(SeO3)/Metal Sulfide Heterostructure. Issue 3 (18th January 2023) - Song, Jinyue; Fan, Hongguang; Bai, Lichong; Wang, Yanpeng; Jin, Yongcheng; Liu, Shuang; Xie, Xiaohui; Zheng, Wansu; Liu, Wei
Abstract: Transitional metal chalcogenide (TMC) is considered as one promising high‐capacity electrode material for asymmetric supercapacitors. More evidence indicates that TMCs have the same charge storage mechanism as hydroxides, but the reason why TMC electrode materials always provide higher capacity is rare to insight. In this work, a Nix Coy Mnz S/Ni(SeO3 ) (NCMS/NSeO) heterostructure is prepared on Ni‐plated carbon cloth, validating that both NCMS and NSeO can be transformed into hydroxides in electrochemical process as accompanying with the formation of SeO3 2‐ and SOx 2− in confined spaces of NCMS/NSeO/Ni sandwich structure. Based on density functional theory calculation and experimental results, a novel space‐confined acidic radical adsorption capacity‐activation mechanism is proposed for the first time, which can nicely explain the capacity enhancement of NCMS/NSeO electrode materials. Thanks to the unique capacity enhancement mechanism and stable NCMS/NSeO/Ni sandwich structure, the optimized electrodes exhibit a high capacity of 536 mAh g −1 at 1 A g −1 and the impressive rate capability of 140.5 mAh g −1 at the amazing current density of 200 A g −1 . The assembled asymmetric supercapacitor achieves an ultrahigh energy density of 141 Wh Kg −1 and an impressive high‐rate capability and cyclability combination with 124% capacitance retention after 10 000 cycles at a large current density of 50 A g −1 . Abstract : In this work a NiSeO3 /Nix Coy Mnz S heterostructure has been prepared as the electrode for aqueous supercapacitors, achieving an impressive energy density of 141 Wh kg −1 which can rival most supercapacitors with organic electrolyte.